Increased regurgitant flow causes endocardial cushion defects in an avian embryonic model of congenital heart disease. (17th February 2017) - Ford, Stephanie M.; McPheeters, Matthew T.; Wang, Yves T.; Ma, Pei; Gu, Shi; Strainic, James; Snyder, Christopher; Rollins, Andrew M.; Watanabe, Michiko; Jenkins, Michael W.
Abstract: Background: The relationship between changes in endocardial cushion and resultant congenital heart diseases (CHD) has yet to be established. It has been shown that increased regurgitant flow early in embryonic heart development leads to endocardial cushion defects, but it remains unclear how abnormal endocardial cushions during the looping stages might affect the fully septated heart. The goal of this study was to reproducibly alter blood flow in vivo and then quantify the resultant effects on morphology of endocardial cushions in the looping heart and on CHDs in the septated heart. Methods: Optical pacing was applied to create regurgitant flow in embryonic hearts, and optical coherence tomography (OCT) was utilized to quantify regurgitation and morphology. Embryonic quail hearts were optically paced at 3 Hz (180 bpm, well above intrinsic rate 60–110 bpm) at stage 13 of development (3–4 weeks human) for 5 min. Pacing fatigued the heart and led to at least 1 h of increased regurgitant flow. Resultant morphological changes were quantified with OCT imaging at stage 19 (cardiac looping—4–5 weeks human) or stage 35 (4 chambered heart—8 weeks human). Results: All paced embryos imaged at stage 19 displayed structural changes in cardiac cushions. The amount of regurgitant flow immediately after pacing was inversely correlated with cardiac cushion size 24‐h post pacing ( P value < .01). The embryos with the most regurgitant flow and smallest cushions after pacing had a decreased survival rate at 8 days ( P < .05), indicating that those most severe endocardial cushion defects were lethal. Of the embryos that survived to stage 35, 17/18 exhibited CHDs including valve defects, ventricular septal defects, hypoplastic ventricles, and common AV canal. Conclusion: The data illustrate a strong inverse relationship in which regurgitant flow precedes abnormal and smaller cardiac cushions, resulting in the development of CHDs.